Effects of hospitalization on functional status and health-related quality of life of patients with COVID-19 complications: a literature review - Oliveira, Miriã Cândida; M. Carrijo, Marilúcia; R. Afonso, João Pedro; S. Moura, Ricardo; R. J. Oliveira, Luís Filipe; L. Fonseca, Adriano; V. C. B. Melo, Vinicio; M. Lino, Maria Eduarda; N. Sousa, Beatriz; R. P. Póvoa, Elisângela; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Due to the clinical situations faced, patients with COVID-19 who survive the intensive care unit (ICU) are at greater risk of developing post-intensive care syndrome (PICS), characterized by typical physical, psychological and cognitive consequences in the post hospital discharge. Given this situation, it is important to assess these patients for the presence of musculoskeletal and psychosocial changes, so that they are referred to an outpatient and/or home rehabilitation program. Objective: to identify in the scientific literature the effects of hospitalization on the functional status and health-related quality of life of patients with complications from COVID-19. Methods: Searches were performed for scientific articles indexed in the MEDLINE database (accessed by Pubmed), between the years 2019 to 2022. Articles that met the inclusion and exclusion criteria determined to compose this study were included. Results: from a total of 524 articles found in the literature, only 15 met the inclusion criteria and were included in the study. The sample was represented by eight cross-sectional studies and seven cohort studies, and the main outcomes found to assess functional status were the six minute walking test the Post-COVID-19 Functional Status scale and for quality of life the EuroQol visual analogue scale and the Short form-36. Conclusion: With this literature review, it can be concluded that patients hospitalized for complications of COVID-19 showed a significant decline in functional status and health-related quality of life.However, updates are necessary to characterize the symptoms and persistent sequelae in the post-COVID-19.